Ecolinguistics in Bangladeshi Secondary-Level English Textbooks: A Corpus Analysis - Awal, Abdul (Colombian Applied Linguistics Journal, 2025)
Ecolinguistics has developed over the past five decades in response to ecological crises and the growing demand for an ecological perspective within linguistics (Zhou, 2021). This study examines the integration of environmental content in 'English for Today Classes Nine-Ten', a secondary-level textbook used in Bangladesh, a country facing a range of environmental challenges. Employing both qualitative and quantitative methods, including the use of AntConc and semantic prosody analysis, the study assessed the frequency, context, and presentation of ecological themes such as sustainability, conservation, and environmental awareness. The findings revealed that ecological terms are included in the textbook inconsistently and with limited diversity, which may hinder students' development of environmental awareness. The research aimed to influence curriculum development and educational policies, underlining the need to incorporate varied and recent environmental issues into educational materials. Therefore, this study emphasizes the need for a more comprehensive inclusion of ecological elements to promote ecolinguistic awareness among students. It contributes to ecolinguistics by recommending improvements in environmental representation in English curricula. Additionally, it offers valuable insights for educators and policymakers to enhance students' environmental literacy and promote sustainable development.